Passing the buck: Corporate restructuring and the casualisation of employment. (1st July 2011) - Ursula Huws
Abstract : This article starts by looking critically at the contested concept of work flexibility, tracing the ambiguities inherent in it to the contradictions embodied in the 'special deals' struck between capital and labour in the third quarter of the 20th century. It then goes on to discuss the new forms of employment casualisation – and resulting precariousness – that have arisen since that period within the 'formal' economy, arising from the processes of financialisation, globalisation and corporate restructuring, before introducing the contents of this volume. It concludes with some general reflections on precariousness.